Preparation and Characterization of Bletilla striata Polysaccharide/Polylactic Acid Composite - Yang, Renyu (Molecules, 2019)
Polylactic acid (PLA) is limited in its application due to its high price, high brittleness and low glass-transition temperature. Modification methods are currently used to overcome these shortcomings. In this study, Bletilla striata polysaccharide (BSP) was blended with PLA by a solvent method. DMA data showed that the BSP/PLA film had a higher glass-transition temperature, and the glass-transition temperature of the film showed an extreme value of 68 °C when the proportion of the chalk polysaccharide was 0.8%. TG data indicates that the composite film material has good thermal stability. Tensile tests show that the composite film is improved in rigidity and elasticity compared to the pure PLA film. The blending modification of PLA with white peony polysaccharide not only reduces the cost of PLA, but also improves the thermal and mechanical properties of PLA.